Respuesta :

Answer:

The answer is (A) (-6,4).

Step-by-step explanation:

First you have to multiply the first equation by 6 and the second equation by 4. Then next you subtract the second equation from 1.

30x + 24y = - 84

12x + 24y = 24

18x + 0. = - 108

=> 18x = - 108

=> x = - 108 / 18

=> x = - 6

Then for the next step

then put in x = - 6 in equation 2 and solve for y

( 3x + 6y = 6)

(3×(-6) + 6y = 6)

( - 18 + 6y = 6)

( 6y = 18 + 6 )

( 6y = 24)

(y = 4 )

(I really do hope this helps!!!)

The answer for you question is option A